2007
DOI: 10.1017/s1368980007000717
|View full text |Cite
|
Sign up to set email alerts
|

Drugs in the treatment of obesity: sibutramine, orlistat and rimonabant

Abstract: Background: Modification of lifestyle is the main therapeutical approach in the treatment of obesity, but use to fail on long terms of time. Addition of anti-obesity drugs allows keeping the weight loss during years and improving obesity-related comorbidities. Methods: This review is an actualisation on efficacy, safety and tolerability of the approved drugs on the long-term treatment of obesity (orlistat and sibutramine). New indications and effects of their use far beyond the weight loss are as well commente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…The addition of sibutramine to behaviour therapy has been found to be more effective than adding a placebo. 35 It might be hypothesized from the present data that sibutramine is more effective in people with less effective response inhibition. To reduce impulsivity an effective treatment strategy might be to train response inhibition.…”
Section: Discussionmentioning
confidence: 68%
“…The addition of sibutramine to behaviour therapy has been found to be more effective than adding a placebo. 35 It might be hypothesized from the present data that sibutramine is more effective in people with less effective response inhibition. To reduce impulsivity an effective treatment strategy might be to train response inhibition.…”
Section: Discussionmentioning
confidence: 68%
“…The optimal strategy for reversing obesity must consider the early stages of IR, and changes in lifestyle are also crucial [39]. Physical activity increases metabolic rate and energy expenditure [40]; however, this approach is short-term in duration and fat accumulation is usually observed [39].…”
Section: Fenugreek (Trigonella Foenum-graecum L)mentioning
confidence: 99%
“…Drugs such as sibutramine, orlistat, and rimonabant have been shown to be efective in improving the lipid proile, lowering blood pressure, glycosylated hemoglobin (in diabetics), and pro-inlammatory cytokine levels, thus reducing cardiovascular risk [41]. Meanwhile, it has been shown that the majority of these drugs instead of lowering cardiovascular risk have the opposite efect, which has led to their removal from the market [42].…”
Section: Pharmacological Treatment For Obesitymentioning
confidence: 99%
“…Orlistat, being an inhibitor of pancreatic and gastric lipases, inhibits the hydrolysis of triglycerides from the diet by up to 30%, thus reducing total caloric intake [41]. Hence, weight loss is not signiicant using this medication only and requires a calorie-restricted regimen.…”
Section: Drugs That Alter Fat Digestionmentioning
confidence: 99%
See 1 more Smart Citation